KNOWLEDGE, ATTITUDE, AND CULTURE INFLUENCE VISUAL INSPECTION WITH ACETIC ACID SERVICE USE - Alifina Izza; Pungky Mulawardhana; Samsriyaningsih Handayani (Jurnal Ners, 2020)
Background: The service use of visual inspection of cervix with acetic acid (VIA) has been low. This technique designed to detect cervical cancer at its earliest stage to prevent the unnecessary burden of its later stages. This study was aimed at showing the influence of knowledge, attitude and culture on the use of VIA service.Methods: This research was a paired case-control study, conducted in 2019 in in the working area of Kalijudan and Mulyorejo Community Health Centers, Surabaya. Ninety eight female respondents of childbearing age were grouped into control and case groups with 49 respondents respectively. Samples were chosen consecutively. Cases were obtained from the health centres’ records, while controls were chosen from cases’ close neighbours. Interviews were conducted in the respondents’ house using closed questionnaires.Results: The multivariate analysis showed that knowledge (p<0.001), attitudes (p=0.012) and culture (p=0.045) affected the use of VIA early detection services.Conclusion: This study pointed out that knowledge, attitude and cultural factors were influential factors in the use of VIA early detection services. Health workers may improve women’s knowledge and attitude through health promotion, and take into account supportive local cultural factors in the program to enhance the use of VIA.